Artistic scarcity in an age of material abundance: President Lyndon Johnson, the National Endowment for the Arts, and Great Society liberalism - Heath, K (Intellect, 2017)
1965 saw President Lyndon Johnson push an incredible number of reform bills through Congress as part of his quest for a Great Society – including legislation to create a National Endowment for the Arts (the federal agency that provides grants to artists and arts organizations in the United States). Public confidence was riding high, the economy was good, and Americans demonstrated a remarkable faith in the capacity of the federal government to solve domestic problems. And yet in this age of abundance, Johnson drew on the rhetoric of scarcity to promulgate his domestic policy. When the President spoke of the cultural aspects of the Great Society he typically emphasized qualitative and quantitative goals, i.e. the power of the arts to improve the quality of life of ordinary Americans and to reduce a perceived imbalance between the haves and the have-nots. Whereas other studies have relegated the cultural aspects of the Great Society to the side-lines, this study places such matters centre stage through an analysis of the rationales behind the creation and early programming of the Endowment. In so doing, it illuminates the inherent contradictions of, and tensions within, American liberalism in the mid-1960s.